2014
DOI: 10.1128/genomea.00750-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of the Onion Center Rot Pathogen Pantoea ananatis PA4 and Maize Brown Stalk Rot Pathogen P. ananatis BD442

Abstract: Pantoea ananatis is an emerging phytopathogen that infects a broad spectrum of plant hosts. Here, we present the genomes of two South African isolates, P. ananatis PA4, which causes center rot of onion, and BD442, isolated from brown stalk rot of maize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…To date, the genomes of 22 P. ananatis strains have been sequenced (Table ). The main focus of these genome sequencing projects has been on phytopathogenic isolates, including strains from pineapple, rice, Eucalyptus , cotton, maize and onion (Adam et al ., ; Choi et al ., ; De Maayer et al ., ; Medrano and Bell, ; Weller‐Stuart et al ., ). However, a variety of endophytic isolates (Midha et al ., ; Sheibani‐Tezerji et al ., ), plant growth‐promoting strains, isolates with potential biotechnological and biological control applications (Gasser et al ., ; Gkorezis et al ., ; Hara et al ., ; Kim et al ., ; Megías et al ., ; Shi et al ., ; Smith et al ., ; Wu et al ., ) and a clinical isolate (De Maayer et al ., ) have also been sequenced.…”
Section: Pantoea Ananatis In the Genome Sequencing Eramentioning
confidence: 97%
See 2 more Smart Citations
“…To date, the genomes of 22 P. ananatis strains have been sequenced (Table ). The main focus of these genome sequencing projects has been on phytopathogenic isolates, including strains from pineapple, rice, Eucalyptus , cotton, maize and onion (Adam et al ., ; Choi et al ., ; De Maayer et al ., ; Medrano and Bell, ; Weller‐Stuart et al ., ). However, a variety of endophytic isolates (Midha et al ., ; Sheibani‐Tezerji et al ., ), plant growth‐promoting strains, isolates with potential biotechnological and biological control applications (Gasser et al ., ; Gkorezis et al ., ; Hara et al ., ; Kim et al ., ; Megías et al ., ; Shi et al ., ; Smith et al ., ; Wu et al ., ) and a clinical isolate (De Maayer et al ., ) have also been sequenced.…”
Section: Pantoea Ananatis In the Genome Sequencing Eramentioning
confidence: 97%
“…Between 4026 ( P. ananatis LMG 20103) and 4698 ( P. ananatis PA4) proteins are encoded on the genomes. The genome of all strains incorporates a single large chromosome and a universal large plasmid, LPP‐1, which ranges in size between 280.8 and 352.8 kilobases (kb) and codes for between 238 and 320 proteins (Choi et al ., ; De Maayer et al ., ; Weller‐Stuart et al ., ). The presence of additional plasmids cannot be excluded (Ismail et al ., ), particularly in the strains with larger genomes, as the majority of the genomes are draft sequences.…”
Section: Pantoea Ananatis In the Genome Sequencing Eramentioning
confidence: 97%
See 1 more Smart Citation
“…P. ananatis is a phytopathogen that infects a wide range of crop and forest plants such as maize (Miller et al, 2016), rice (Watanabe et al, 1996), onion (Gitaitis et al, 2002;Weller-Stuart et al, 2014), eucalyptus (Coutinho et al, 2002;De Maayer et al, 2010) and it has occasionally been reported as a clinical isolate infecting workers with plant material or from immunocompromised individuals in hospital settings. The number of reports linking the TU with human disease is scarce (De Baere et al, 2004;De Maayer et al, 2012;Manoharan et al, 2012).…”
Section: Safety Concernsmentioning
confidence: 99%
“…This bacterium has been isolated from various habitats, such as plants ( 1 ), soil ( 2 ), water ( 3 ), and aviation fuel tanks ( 4 ). While there have been reports of human infection ( 5 , 6 ), P. ananatis is known primarily as a pathogen in plant hosts, such as rice ( 7 ), maize ( 8 ), and onion ( 9 ). Recent findings, however, have also highlighted the existence of beneficial strains that live on the hosts as commensals or plant growth promoters ( 10 12 ).…”
Section: Genome Announcementmentioning
confidence: 99%